On VO vs. OV in Southeast Asia - Benedict, Paul K. (2024)
It has now become conventional wisdom in Southeast Asian linguistics that Proto-Sino-Tibetan is to be reconstructed as verb-final, as reflected in Tibeto-Burman, with the Chinese VO word order secondary, e.g. at the recent International Conference on Sino-Tibetan Languages and Linguistics XXVI in Osaka, both Matisoff and LaPolla presented papers to this effect. The explanations for this vary from scholar to scholar; the writer has emphasized an apparent substratum factor inasmuch as both blocs of Sino-Tibetan that present VO, viz. Chinese and Karen, lie on the east, where they overlie Austro-Tai (Austronesian /Kadai/Hmong-Mien), with the same VO feature. In any event, the historical picture conventionally drawn in Southeast Asia has a basic distinction between a monosyllabic Sino-Tibetan of OV type and a sesquisyllabic (Matisoffs term) Mon-Khmer of VO type, shared by Kadai and Hmong-Mien as well as by Chamic and Malay.